PENGARUH PENGALAMAN AUDITOR, SKEPTISISME PROFESIONAL DAN TEKANAN WAKTU TERHADAP PENDETEKSIAN KECURANGAN DI PERWAKILAN BPKP PROVINSI BENGKULU - Lismawati Lismawati; Novita Sari; Mifta Ismalia (Jurnal Akuntansi dan Keuangan, 2021)
This study aims to prove the influence of the auditor's competence, professionalism and ethics on audit quality. This study uses a quantitative approach. Respondents in this study were all auditors in the Bengkulu Province Inspectorate as many as 45 respondents.. The selection of samples tested in this study using purposive sampling. The data analysis technique uses multiple regression analysis.The results of this study indicate that competence affects audit quality. Professionalism also has an effect on audit quality. Auditor ethics also proved to influence audit quality.